The Book Azf Ala Vatar el-Nas ol-Sheri from a Critical Point of View - Fatemeh Ghaderi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
By definition, criticism is the task of examining the validity of a work of art or literature. Like other disciplines, it is based on specific rules and regulations. Once a work is criticized, its strengths and weakneses are revealed. In this regard, ‘Azf Ala Vatar el-Nas ol-Sheri’ (Playing the Strings of Poetry) by Omar Mohammad al-Talib is evaluated as a book that seeks to grasp the content through the text analysis. The analysis is conducted by sticking to various aspects of literary criticism and avoiding theoretical subjects. The present study aims to evaluate the book for its strengths and weak points in an objective and unbiased manner. The research method is descriptive for the structure and descriptive-analytical for the content of the book. As the results of the content analysis indicate, the author’s goal is successfully fulfilled. In structural terms, however, the book is beset with certain shortcomings, which the author and the publisher are advised to mend.